2016
DOI: 10.3168/jds.2016-10956
|View full text |Cite
|
Sign up to set email alerts
|

Management characteristics, lameness, and body injuries of dairy cattle housed in high-performance dairy herds in Wisconsin

Abstract: The objective of this study was to benchmark the prevalence of lameness, hock and knee injuries, and neck and back injuries among high-performance, freestall-housed dairy herds in Wisconsin. A random selection of 66 herds with 200 or more cows was derived from herds that clustered with high performance in year 2011 Dairy Herd Improvement records for milk production, udder health, reproduction, and other health parameters. Herds were surveyed to collect information about management, facilities, and well-being. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 49 publications
(70 reference statements)
5
65
6
1
Order By: Relevance
“…Hock lesion prevalence in this study was less (17.4%) than previously reported in other studies, where prevalence ranged from 42 to 81% (Weary and Taszkun, 2000;von Keyserlingk et al, 2012). Cook et al (2016) found that the prevalence of all hock lesions in highproducing (>40 kg of daily milk production) herds in Wisconsin was 50.3% and severe hock lesion prevalence was 12.2%. As mentioned previously, 93% of the herds in the current study were housed on deep beds, with only approximately 7% of farms using mattress-based freestalls.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Hock lesion prevalence in this study was less (17.4%) than previously reported in other studies, where prevalence ranged from 42 to 81% (Weary and Taszkun, 2000;von Keyserlingk et al, 2012). Cook et al (2016) found that the prevalence of all hock lesions in highproducing (>40 kg of daily milk production) herds in Wisconsin was 50.3% and severe hock lesion prevalence was 12.2%. As mentioned previously, 93% of the herds in the current study were housed on deep beds, with only approximately 7% of farms using mattress-based freestalls.…”
Section: Discussioncontrasting
confidence: 68%
“…Our animal health assessment indicated that the farms in the current study had lower lameness prevalence (18.3%) than some previous studies that reported 25 to 30% lameness prevalence (also by scoring the high-producing pen on freestall farms; Espejo et al, 2006;Ito et al, 2010). However, some more recent studies (Cook et al, 2016;Adams et al, 2017) reported lower lameness prevalence of 9.6 and 13.2% and severe lameness prevalence of 2.5 and 1.7%. Discrepancies in these values could result from the fact that previous studies included a variety of stall surfaces in their evaluation.…”
Section: Discussioncontrasting
confidence: 54%
“…A third possible consequence of being later in the milking order relates to the extra time spent standing in the dairy yard before milking rather than time away from the paddock. The surface on which cows walk can affect the prevalence of lameness and the experience for cows that are lame (Sauter-Louis et al, 2004;Kremer et al, 2007;von Keyserlingk et al, 2009;Cook et al, 2016). Depending on the dairy yard surface and the condition of the paddock, the effect of being at the beginning or end of the milking order might be positive or negative in terms of animal welfare.…”
mentioning
confidence: 99%
“…Cattle mobility scoring is becoming one of the widely accepted method of assessing potential welfare effects. But no such tool existed two years ago for finished cattle; however, it is important to mention that several lameness studies have been conducted on farms, showing that it is a serious welfare problem (von Keyserlingk, Barrientos, Ito, Galo, & Weary, 2012;Cook, Hess, Foy, Bennett, & Brotzman, 2016). Mobility scoring is an animal-based measure.…”
Section: Behavioral Indicatorsmentioning
confidence: 99%